2020
DOI: 10.1002/pan3.10174
|View full text |Cite
|
Sign up to set email alerts
|

Shapeshifting attachment: Exploring multi‐dimensional people–place bonds in place‐based citizen science

Abstract: Research on citizen science programmes has highlighted that they can foster science content and knowledge gain, enhance pro‐environmental behaviour and cultivate civic action among participants. Especially in the case of place‐based citizen science, which requires hands‐on repeated activity in an out‐of‐door setting through a scientific lens, evidence suggests that some of these outcomes may be linked to the unique people–place relationships and interactions afforded by such programmes. Even still, studies th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 72 publications
(179 reference statements)
0
8
0
Order By: Relevance
“…Citizen science programs bring place-based education into informal learning (National Research Council, 2009). "Sense of place" has been described as the emotional, generative interaction between a person and a place, a sense which is emphasized and reified by experiences with place-based citizen science (Haywood 2014;Newman et al, 2017;Haywood et al, 2021). Evaluation of the Mosquito Mappers research internship demonstrated that the local citizen science fieldwork successfully used a sense-of-place pedagogy to motivate students.…”
Section: Discussionmentioning
confidence: 99%
“…Citizen science programs bring place-based education into informal learning (National Research Council, 2009). "Sense of place" has been described as the emotional, generative interaction between a person and a place, a sense which is emphasized and reified by experiences with place-based citizen science (Haywood 2014;Newman et al, 2017;Haywood et al, 2021). Evaluation of the Mosquito Mappers research internship demonstrated that the local citizen science fieldwork successfully used a sense-of-place pedagogy to motivate students.…”
Section: Discussionmentioning
confidence: 99%
“…These experiences are typical of memorable embodiment experiences in wildlife tourism (and not exclusively diving) [38]. The divers' narratives often revolved around personal and environmental contexts which contribute to place attachment, with emphasis on place dependence, place identity, nature bonding and environment bonding [39].…”
Section: Marine Lifementioning
confidence: 99%
“…An under-researched area of citizen science, and more widely environmental stewardship, is the emotional bond between a person and a place, termed 'place attachment' (PAT). Haywood et al (2021) delineate a revised three-dimensional model of PAT for citizen science (after Raymond et al, 2010) and apply it to the COASST program. The three dimensions comprise personal, community and natural environment components, with seven major constructs across them.…”
Section: Yet Citizen Science Research Has Only Recently Begun To Cons...mentioning
confidence: 99%
“…Haywood et al. (2021) delineate a revised three‐dimensional model of PAT for citizen science (after Raymond et al., 2010) and apply it to the COASST program. The three dimensions comprise personal, community and natural environment components, with seven major constructs across them.…”
Section: Questions and Themes Covered By Papers In The Special Featurementioning
confidence: 99%
See 1 more Smart Citation